Die Intensiv- und Notfallmedizin in der internistischen Weiterbildung - Riessen, R.; Busch, H. J.; John, Stefan (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Intensive care and emergency medicine are extremely important for the treatment of patients with acute and severe medical conditions. While other internal medicine specialties are progressively focused on specific organ systems or diseases, rotations of residents into the intensive care unit (ICU) or the emergency department (ED) are an important part of their training in general internal medicine. Here they can acquire many of the diagnostic and therapeutic skills required in their curriculum. All internal medicine residents in Germany therefore must complete at least a 6 month rotation in the ICU and the ED. For training programs in general internal medicine, the German Society for Medical Intensive Care and Emergency Medicine (Deutsche Gesellschaft für Internistische Intensivmedizin und Notfallmedizin) asks the German State Medical Councils to accept rotations in the ICU and the ED for 15 months each. After adding an ICU or ED fellowship, these internists would be ideally qualified for much needed attending and leadership positions in the ICUs and EDs and would have a better perspective for a scientific career in these fields. In addition, ICU and ED fellowships of internists from other specialties should be supported.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Advanced training regulations; Curriculum; Emergency service; hospital; History; medical specialty training; Specialties; internal medicine